The egyptian souvenir - Flagan, Mary (Italy ELI - Teen Readers, 2010)
Sally wants to be a detective and her hobby is solving mysteries. But this time the mystery is really difficult! Read about Sally's adventures and enjoy !
Contents, Introduction and main Characters.
Keywords: Story; Crime; Language Learning; Pre-Intermediate Level; Classroom activities